ZMYND8 is a primary HIF coactivator that mediates breast cancer progression. (4th July 2018) - Chen, Yan; Wang, Yingfei; Luo, Weibo
ABSTRACT: Epigenetic regulator plays a pivotal role in breast cancer progression. We recently demonstrated that the epigenetic reader zinc finger MYND-type containing 8 (ZMYND8) mediates breast cancer progression and metastasis by activating hypoxia-inducible factor (HIF). This discovery provides new insights into the molecular mechanism underlying HIF activation and breast cancer progression.